Dental Implant Osseointegration Inhibition by Nicotine through Increasing nAChR, NFATc1 Expression, Osteoclast Numbers, and Decreasing Osteoblast Numbers - Nilawati, Nina; Widyastuti, Widyastuti; Rizka, Yoifah; Kurniawan, Hansen (European Journal of Dentistry, 2022)
Objective The success of dental implants is determined by the osteointegration process. Many studies state that smoking cigarettes can inhibit osseointegration, but the inhibition mechanism is still unclear.The aim of this study was to identify and analyze the effect of nicotine on the inhibition of dental implant osseointegration through the expression of nicotinic acetylcholine receptor (nAChR), nuclear factor of activated T cells cytoplasmic 1 (NFATc1), osteoclast, and osteoblast numbers.Materials and Methods This study is an experimental study of 16 New Zealand rabbits, randomized across two groups. Group 1 (eight rabbits) was a control group, and group 2 (eight rabbits) was a treatment group. The treatment group was given 2.5 mg/kg body weight/day of nicotine by injection 1 week before placement of the implant until the end of research. Observations were made in the first and the eighth week by measuring the number of osteoblast and osteoclast by immunohistology test and the expression of nAChR and NFATc1 by immunohistochemistry test.Statistical Analysis Data was analyzed using a one-way analysis of variance and Student's t-test. A p-value of < 0.05 was considered statistically significant.Results Significant differences were found between the control and treatment groups (p < 0.05). Results showed that nicotine increases the expression of nAChR and decreases the number of osteoblasts and the expression of BMP2 and osteocalcin.Conclusion Nicotine inhibits the osseointegration of dental implants by increasing nAChR, NFATc1, osteoclast numbers, and decreasing osteoblast numbers.
Keywords: dental implant; nicotine; nAChR; NFATc1; osteoclast; osteoblast; osseointegration